UTILIZATION OF CRAB SHELL WASTE AS A SPHERICAL CHITOSAN (CH-Z SPHERICAL) COMPOSITE TO REDUCE HARD WATER - Alawiyah, Tuty; Azmiyati, Uzlifatul (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2019)
In this research, have perfomed the synthesis of chitosan from crab shell waste as a Chitosan/Zeolite (Ch-Z spherical) composite to reduce water hardness. The synthesis of chitosan can be done in three stages, namely demineralization, deproteination, depigmentation, and deacetylation. The stages of Chitosan/Zeolite Spherical (Ch-Z Spherical) synthesis were made with variations in the weight of chitosan: zeolite (w /w) 1: 0.5; 1: 1; 1:1.5 using Crosslinking Sodium tripolyphospat. The characterization results by using FT-IR for chitosan-zeolite weight variations at wavelengths of 4000-450 cm-1 show a typical IR spectrum for chitosan / zheolite Spherical (Ch-Z Spherical) successively at wavelengths of 1639 cm-1, 1638 , 71 cm-1, and 1638.58 cm-1 which is the -Câ¼N strain or structural change (deformation) of NH2. The chitosan-zeolite spherical (Ch-Z spherical) composite was applied to reduce the metal Ca (II) and Mg (II) which can cause hardness in water. The effectiveness of 0.5 gram Ch-Z Spherical composites, we tested the variation of composite weights 0.1,Â 0.2, 0.4, 0.6, 0.8, and 1.2 gr as adsorbents of Ca (II) metal ) and Mg (II) with a concentration of 1000 ppm in 1 hour with the stirring process. The results obtained by a decrease of 99.69% at a weight of 0.6 grams and experienced constant along with an increase in the mass of adsorbent. While the effectiveness of the Spherical Ch-Z composite in reducing the concentration of Mg (II) by 99.4% in a weight variation of 1.2 gr. This shows the formation of active sites contained in the Spherical Ch-Z composite. Metal adsorption capacity of Ca (II) and Mg (II) obtained in this study amounted to 498 mg/g and 23.7 mg /g